VD_FINDINFO AI 94/18 - 42/2020 vom 4. Februar 2020 - VD Tribunal cantonal (2020)
APTITUDE À LA RÉADAPTATION, RENTE D'INVALIDITÉ, RHUMATISME, AFFECTION PSYCHIQUE | 28 LAI, 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA